Revealing the Secret of Ugamo Malim in Batak Land - Santa Rosa Br Pardosi; Hana Maria Br Sitorus; Deang Sri Mustika Silalahi; Dahlia Naibaho; Achmad Yuhdi (Britain International for Academic Research (BIAR) Publisher, 2023)
The purpose of this is to describe the strategy, existence and sentiment of the minority parmalim community of Batak Toba ethnic community in the Huta Tinggi village of Laguboti Toba Samosir. The method applied in this research is ethnography with the type of social humanities research. The data were obtained by conducting observations, interviews, documentation, and document studies which were then processed by using Spradley's data analysis techniques. The results obtained from this study are that the strategies of parents, youth and parmalim leaders, then the existence of ugamo Malim spread throughout Indonesia. There are 139 people who live in Laguboti, Huta Tinggi village. The believers of this belief are spread in 38 regions which are passed on by the young parmalim. The sentiments of society are normal as well.